An Efficient In Vitro Shoot Organogenesis and Comparative GC-MS Metabolite Profiling of Gaillardia pulchella Foug - Mahima Bansal; A. Mujib; Yashika Bansal; Yaser Hassan Dewir; Nóra Mendler-Drienyovszki (Horticulturae, 2024)
Gaillardia pulchella Foug. is a widely studied plant because of its high pharmacological and ornamental value. The leaves of G. pulchella were used for inducing callus and subsequent plant regeneration as it is the primary source of phytocompounds. The purpose of the present investigation was to formulate an in vitro propagation method for Gaillardia by using leaf explants in MS (Murashige and Skoog) medium. The best callus induction was observed on high (2.0 mg/L) α-naphthalene acetic acid (NAA) and a low (0.5 mg/L) 6-benzylaminopurine (BAP) with callus induction frequency of 91.66%. The leaf callus also demonstrated high caulogenesis ability (95.83%), with an average 5.2 shoots/callus mass at 0.5 mg/L BAP and 2.0 mg/L NAA. Indole Acetic acid (IAA) at 1.0 mg/L had the maximum rooting percentage (79.17%) with 12.4 roots per shoot. Rooted plantlets were later transferred to greenhouse conditions, showing a survivability rate of 75–80%. The physiological parameters, i.e., phenolic compounds and the flavonoids’ level, in the DPPH assay were higher in leaves obtained in vitro compared to callus formed from leaves and field-obtained (mother) leaves. Gas chromatography–mass spectrometry (GC–MS) analysis of methanol extracts of leaves (in vivo and in vitro) and leaf callus presented a wide array of compounds. In callus extract, some 34 phytocompounds were identified. Some of them were 3-hydroxy-2,3-dihydromaltol (25.39%), isoamyl acetate (11.63%), palmitic acid (11.55%), 4-methyloxazole (7.54%), and 5-methoxypyrrolidin-2-one (7.49%). Leaves derived in vivo and in vitro had 45 and 28 phytocompounds, respectively, belonging to different classes like lignans, phenols, terpenoids, alkaloids and fatty acids, etc. Those findings demonstrated that the leaf derived callus and the leaves are the potential stable source of several compounds with medicinal importance. The developed protocol may provide an alternative source of compounds without affecting wild flora.